(untitled) (Journal of the College of Education for Women, 2019)
There is a relationship between the sizes of urban centers and regionaldevelopment, concerning the role that these centers are playing indevelopmental process.The research assume that the urban system in the governorate, hasbeen affected by the external environment due to the religious dominance ofKerbla city.The research is composed of three sections, the first is a theoreticalbackground, which focus upon the general directions of the models andtheories that have a relationship with the subject. The second is a practicalpart aims at determination the characteristics of the sizes of the cities in thegovernorate. Depending upon of previous part, i.e., the practical part section three deals with suggestions that aim at developing the urban policy in thegovernorate.The results have shown, the primate pattern is common feature in theurban system owing to over urbanization of Kerbla city, which extremes thelaw of primate city that has been established by Jefferson. Thus, coreperipherymodel that Friedmann has Firmed appears due to the reduction ofinterdependency between the cities in governorate.The research suggest, that the governorate has to follow Agropolitandevelopmentstrategy, especially in the southern and western parts, in orderto decrease the unbalance urban development.